Phytochemical Screening and Antimicrobial Activity of Homoeopathic Dilutions of Myristica sebifera against Staphylococcus aureus - Shaw, Niharika; Singh, Supriya; Paul, Subhrajit; V., Kumaravel; M., Raja (Homœopathic Links, 2023)
Background The Anti-Microbial Resistance (AMR) has trend of increasing morbidity and mortality affecting the management of variety of infectious disorders in humans. Our skin is native to the bacterium Staphylococcus aureus, which is also a frequent source of infections in both the general population and healthcare settings. On the other side, Myristica sebifera is known for its great antiseptic activity in Homoeopathy.Objective This study was aimed to explore the phytoconstituents & antimicrobial activity of Homoeopathic preparation of Myristica sebifera 12C, 30C & 200C.Materials and Methods Myristica sebifera 12C, 30C & 200C were tested for identification of its phytoconstituents and antimicrobial activity was evaluated following Kirby-Bauer Disk Diffusion (KBDD) method according to clinical and laboratory standard (CLSIM44 A) with slight modifications. The diameter of zone of inhibition was measured and compared with Gentamicin (Positive Control) & Alcohol (62% & 91% as Negative Controls). The experiment was performed thrice to check the accuracy and reproducibility.Result Myristica sebifera 12C & 30C showed maximum zone of inhibition up to (10.33 ± 1.52 & 11.67 ± 1.52 respectively) against Staphylococcus aureus when compared to control (Alcohol 62% & 91%) as 6.00 ± 0.00.Conclusion Phytochemical studies showed presence of alkaloids and carbohydrate in Myristica sebifera 12C and 30C. The maximum percentage of zone of inhibition (94%) was found in Myristica sebifera 30C followed by Myristica sebifera 12C (72%). This antimicrobial study suggests that Myristica sebifera 12C & 30C could be helpful for treating the disorders caused by Staphylococcus aureus.
Keywords: homoeopathy; Myristica sebifera; phytochemical analysis; Clinical Laboratory Standards Institute (CLSI) guidelines; Kirby-Bauer disk diffusion (KBDD) method